10d+3=7d+15

Simple and best practice solution for 10d+3=7d+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10d+3=7d+15 equation:


Simplifying
10d + 3 = 7d + 15

Reorder the terms:
3 + 10d = 7d + 15

Reorder the terms:
3 + 10d = 15 + 7d

Solving
3 + 10d = 15 + 7d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-7d' to each side of the equation.
3 + 10d + -7d = 15 + 7d + -7d

Combine like terms: 10d + -7d = 3d
3 + 3d = 15 + 7d + -7d

Combine like terms: 7d + -7d = 0
3 + 3d = 15 + 0
3 + 3d = 15

Add '-3' to each side of the equation.
3 + -3 + 3d = 15 + -3

Combine like terms: 3 + -3 = 0
0 + 3d = 15 + -3
3d = 15 + -3

Combine like terms: 15 + -3 = 12
3d = 12

Divide each side by '3'.
d = 4

Simplifying
d = 4

See similar equations:

| 4x^3-18x^2+3=0 | | 4x+4x=10+20 | | 12-8=10+4 | | 4m=8-x | | (-3r+4+11+4r)-(5r+3)= | | 5x-2=3x+5 | | 10(2a+a)=230 | | 6(6+(-2c))=60 | | 3+5x=50+x | | 2(t-3)-4=t-3(t+1) | | 3.6=1.6w+24 | | -7-m=-8(8-7m) | | 4r+3=7-(-4r) | | -3x+40=1 | | =-25x+9 | | 4n=368 | | 7(x-1)=11.2 | | =5x-3[(11x-5)-(x-2)] | | 3-2(a-1)=4a-13 | | 5.2=2c-9 | | z^2+2iz-3i=0 | | 4(x-2)+12=2(5-2x) | | 20+X=51 | | 6e-8=16 | | -y+7(6+2y)= | | 2x+12=68+6x | | 5x+2y^2=3 | | (h-78)/9(1)+(-13)+50-(78*.25)=-20 | | 4(2x-1)=-28 | | 4(x-8)=0 | | 22=t | | 8+1.25=16.75 |

Equations solver categories